(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
A maximum power point tracking (MPPT) algorithm is utilized in this study for photovoltaic systems that provide resistive bourdons. The PV module and the bourdon both contain a DC-DC boost conversion at their respective locations in order to permit matching. MPPT, which is governed by the EHCA (Enhance Hill Climbing algorithm) algorithm, is responsible for regulating the power conversion. Through the application of the algorithm to a controller, the purpose of this study is to strengthen the source program in order to achieve the best possible equilibrium between speed and precision. There are two photovoltaic modules that are tested under conditions that are comparable to one another. In the beginning, an EHCA-MPPT control is implemented, and in the later stages, the CHCA (Conventional hill climbing algorithm) MPPT control is utilized. A reaction time of 0.3 seconds and a reduction in fluctuation power of 4% were achieved by the upgraded algorithm, according to the data, which highlight a significant improvement in rate for the algorithm. The precision of the algorithm is considered to be adequate in relation to the traditional system and the algorithms that are mentioned in the literature. These values are considered to be satisfactory.